Let’s groove: Attachment techniques of Eurasian elk (Alces alces) tooth pendants at the Late Mesolithic cemetery Yuzhniy Oleniy Ostrov (Lake Onega, Russia) - Mannermaa, Kristiina; Rainio, Riitta; Girya, Evgeny; Gerasimov, Dmitry (Archaeological and Anthropological Sciences, 2020)
Peer reviewed